Communication with Compassion in the #KlikBiarSelamat Campaign - Fitmi , Khaira; Saefihim; Hikmawan, Ratu Assyifa Khairunnisa Noor Rizky; Arifan, Fahmi (Jobmark: Journal of Branding and Marketing Communication, 2020)
The #KlikBiarSelamat campaign communicates the importance of wearing a helmet correctly when riding a motorbike. This article dissects the case of the advertising campaign and hashtag for using helmets from the Komunikasih theory (communication with compassion) perspective. The campaign was initiated with sincere intentions and goals: to convey constructive and selfless messages, send messages and feedback full of compassion, form meaning with empathy, use positive media and provide a loving impact. This study can be an essential reference for campaigners in applying Komunikasih in persuasion communication activities to produce positive and peaceful results without counterproductive conflict.